2019
DOI: 10.1186/s41687-019-0161-y
|View full text |Cite
|
Sign up to set email alerts
|

BOMET-QoL-10 questionnaire for breast cancer patients with bone metastasis: the prospective MABOMET GEICAM study

Abstract: BackgroundBone metastasis (BM) is the most common site of disease in metastatic breast cancer (MBC) patients. BM impacts health-related quality of life (HRQoL). We tested prospectively the psychometric properties of the Bone Metastasis Quality of Life (BOMET-QoL-10) measure on MBC patients with BM.MethodsPatients completed the BOMET-QoL-10 questionnaire, the Visual Analogue Scale (VAS) for pain, and a self-perceived health status item at baseline and at follow-up visits. We performed psychometric tests and cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Results were possibly biased as patients with only visceral metastasis were also included, although biphosphonate treatment is not effective in these cases [ 39 ]. The study of Barnadas et al, a subanalysis of patients receiving specific treatment for bone metastatis versus no treatment revealed clinically significant improvement in HRQoL [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results were possibly biased as patients with only visceral metastasis were also included, although biphosphonate treatment is not effective in these cases [ 39 ]. The study of Barnadas et al, a subanalysis of patients receiving specific treatment for bone metastatis versus no treatment revealed clinically significant improvement in HRQoL [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Direct interviews assessing QOL were found to be highly advantageous in guiding healthcare professionals to attain a clear idea about the patient's QOL, to evaluate patient's medical situation and to tailor treatment accordingly so as to avoid medical problem that may negatively affect patient's QOL (35,36) . Barnadas et al, (37) , denotes the necessity to understand impact of cancer disease-associated complications such as anaemia among others, as well as palliative care treatments towards breast cancer patients QOL. Moreover, Chen et al (38) mentions that studies focused on detecting QOL among women suffering from breast cancer is the cornerstone for evaluating clinical situation, clinical decision making as well as health policy or reimbursement decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have only recently reported on physical function and anxiety levels in cancer patients using these PROMIS-Ca question banks. 64,65 The BOMET-QoL, a musculoskeletal oncologyspecific measure, is a 10-item questionnaire that assesses the subjective and physical aspects of metastatic bone disease to identify changes in the HRQOL in metastatic bone disease patients 66,67 (Table 1). SAM was created as a sarcoma-specific PROM and is a 22-item questionnaire that evaluates the physical, emotional, financial, and social well-being as well as patient sexuality 68 (Table 1).…”
Section: Health-related Quality-of-life Measuresmentioning
confidence: 99%